Role of surgery in colorectal liver metastases: Too early or too late? - Dimitroulis, Dimitrios (The WJG Press and Baishideng, 2010)
As colorectal cancer and colorectal liver metastases become a serious public health problem, new treatment modalities are needed in order to achieve better results. In the last decade there has been very important progress in oncology, with new and more effective chemotherapeutic agents administered alone or in combination improving the resectability rate in up to 40% of patients with colorectal liver metastases. Advances in interventional radiology, in particular, with the use of portal vein embolization and radiofrequency thermal ablation are new strategies allowing major liver resections and treatment of small liver metastases or early recurrences. Surgery, however, remains the gold standard strategy with intention to treat. In this review article we will describe the advanced role of surgery in the multidisciplinary approach to colorectal liver metastases, and the clinical problems the liver surgeon has to deal with, such as the resectability of the metastases, the presence of bilobar liver lesions and extrahepatic disease, the impact of chemotherapy in already resectable liver metastases, the problem of vanishing metastases after chemotherapy and the dilemma of staged or combined liver and colon operations and which organ first in the clinical scenario of synchronous colorectal liver metastases.